Rat life - Arnold, Tedd. (New York : Sleuth Speak, 2009)
After developing an unusual friendship with a young Vietnam War veteran in 1972, fourteen-year-old Todd discovers his writing talent and solves a murder mystery.
School Library Journal
Wilson's Junior High School
Wilson's Senior High School
Young Adult.
Young Adult
Keywords: Creative writing -- Juvenile fiction; Vietnam War, 1961-1975 -- Veterans -- Juvenile fiction; Creative writing -- Fiction; Mystery and detective stories; Vietnam War, 1961-1975 -- Veterans -- Fiction; Creative writing -- Fiction; Mystery fiction; Vietnam War, 1961-1975 -- Veterans -- Fiction; Mystery fiction